Mechanical properties of AA7075 aluminium chip reinforced rice husk silica by solid state technique - Mohd Joharudin, Nurul Farahin; Abdul Latif, Noradila; Mustapa, Mohammad Sukri; Badarulzaman, Nur Azam; Supawi, Aiman (Penerbit UTHM, 2020)
Types of reinforcements in Metal Matrix Composite (MMC) are essential to form a better MMC due to the bonding element to the based matrix. This research was carried out based on the recycling of aluminium alloy AA7075 reinforced rice husk silica (natural waste fibres) as MMC. Solid state technique was used to examine the effect of rice husk silica as a reinforcement agent in MMCs. This technique remarkably lower operation costs and resources compared to conventional cast recycling. Recycled aluminium chip AA7075 with the addition of composition as-received untreated and treated rice husk silica (2.5, 5, 7.5, 10, and 12.5 wt%) were used. Treated rice husk was soaked in hydrochloric acid to fasten the burning process at temperatures of 700 and 1000°C. MMC samples were prepared using a cold compaction method by setting of load compaction of 9 tons for 20 minutes. Then, the MMC samples were sintered at a temperature of 552°C. Mechanical properties of MMC were obtained from hardness and compression tests, while optical microscope (OM) and scanning electron microscopy (SEM) were used for microstructural analysis of MMC samples. For mechanical properties, the hardness of MMC was higher at 10 wt% rice husk silica, i.e., 65.93 Hv for untreated, and 69.52 Hv for treated rice husk. These results were based on rice husk silica that burned at 700℃. It found that aluminium chip sample without reinforcement was 53.49 Hv, which is lower than samples at 10 wt% of rice husk silica. For the compressive strength, silica burned at 700℃ indicated rice husk silica at 5 wt% obtained high strength of MMC with 333.63 MPa for untreated, and 322.52 MPa for treated rice husk silica. In comparison, aluminium chip without a reinforcement sample was found to lower strength with 290.47 MPa. Based on this research, the reinforcement of rice husk silica burned at 700℃ has better properties of MMC compared to rice husk silica burned at 1000℃.